1997
DOI: 10.1002/etc.5620160507
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic toxicity of eighteen phthalate esters

Abstract: The extensive database of acute and chronic aquatic toxicity data for 18 phthalate esters was reviewed and summarized for freshwater and saltwater aquatic microorganisms, algae, invertebrates, and fish. Phthalate esters have been tested with six species of microorganisms, including bacteria and protozoans. Fifteen algal species have been tested, including green and bluegreen algae in both freshwater and saltwater. Nineteen freshwater and saltwater invertebrate species inhabiting surface waters and sediments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 181 publications
(46 citation statements)
references
References 71 publications
2
44
0
Order By: Relevance
“…Phthalic acid esters are endocrine-disrupting compounds, which have been shown to reduce the diversity of microbial communities and decline crop quality [31], and are toxic to most aquatic organisms including algae [32]. Higher concentration of DMP inhibits the growth rate, while lower concentration can induce the growth of Cyanobacteria or algae [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Phthalic acid esters are endocrine-disrupting compounds, which have been shown to reduce the diversity of microbial communities and decline crop quality [31], and are toxic to most aquatic organisms including algae [32]. Higher concentration of DMP inhibits the growth rate, while lower concentration can induce the growth of Cyanobacteria or algae [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…PAEs especially the lower molecular weight di-methyl phthalate (DMP), di-ethyl phthalate (DEP), di-n-butyl phthalate (DBP) and butylbenzyl phthalate (BBP) are toxic to aquatic life at concentrations below their aqueous solubilities (Staples et al 1997;Zhou et al 2011). In animal studies, several phthalates and/or its metabolites are shown to disrupt the reproductive functions and are developmental toxicants (Foster 2006;Hotchkiss et al 2010;Howdeshell et al 2008;Mylchreest et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…They are absorbed readily through the skin and the digestive tract and are then distributed to most tissues, even the placenta, as mentioned above. It has been reported that PAEs with alkyl chain lengths of <6 have intrinsic toxicity to aquatic organisms (Staples et al, 1997). All of the research and studies into the distribution and toxicity reminds us to pay more attention to the removal and degradation of these typical, widely used PAEs.…”
Section: Introductionmentioning
confidence: 99%